2014
DOI: 10.1016/j.devcel.2014.05.020
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Plant Stem Cell Quiescence by a Brassinosteroid Signaling Module

Abstract: The quiescent center (QC) maintains the activity of the surrounding stem cells within the root stem cell niche, yet specific molecular players sustaining the low rate of QC cell division remain poorly understood. Here, we identified a R2R3-MYB transcription factor, BRAVO (BRASSINOSTEROIDS AT VASCULAR AND ORGANIZING CENTER), acting as a cell-specific repressor of QC divisions in the primary root of Arabidopsis. Ectopic BRAVO expression restricts overall root growth and ceases root regeneration upon damage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 48 publications
11
180
1
Order By: Relevance
“…Arabidopsis thaliana accession Columbia (Col-0) was used along with previously described mutants: atg5-1 (Thompson et al, 2005), atg7-2 (Chung et al, 2010), bri1-301 (Li and Nam, 2002), bes1-D (Vilarrasa-Blasi et al, 2015; Yin et al, 2002), bin2-1D (Li et al, 2001), bin2-3 bil1 bil2 (Yan et al, 2009). Well characterized DSK2 RNAi lines (Lin et al, 2011) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Arabidopsis thaliana accession Columbia (Col-0) was used along with previously described mutants: atg5-1 (Thompson et al, 2005), atg7-2 (Chung et al, 2010), bri1-301 (Li and Nam, 2002), bes1-D (Vilarrasa-Blasi et al, 2015; Yin et al, 2002), bin2-1D (Li et al, 2001), bin2-3 bil1 bil2 (Yan et al, 2009). Well characterized DSK2 RNAi lines (Lin et al, 2011) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, recent studies have demonstrated that BR signaling pathway is required to regulate hypocotyl cell expansion (Gallego-Bartolomé et al 2012;Li et al 2012;Oh et al 2012), as well as, to promote the transition from meristematic cells to primordial cells in the shoot (Oh et al 2011;Zhiponova et al 2013). In the root apex, BRs are further involved in controlling root growth, both coordinating root meristem size and also root cell elongation Heyman et al 2013;Vilarrasa-Blasi et al 2014;Vragovic et al 2015). In all of these physiological processes BES1/BZR1 complex plays a pivotal role, interacting with several TFs in order to connect other signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Many hormones affect the cell cycle and cell expansion directly or indirectly, including brassinosteroids in the root [87][88][89] and gibberellins, abscisic acid, and ethylene in various development contexts [7,8]; however, cytokinin and auxin are the major hormonal regulators of core cell cycle components [8]. For many plant cells, determination is accompanied by endoreduplication, cell polyploidisation, and cessation of cell proliferation.…”
Section: Cytokinins and Auxins And The Cell Cyclementioning
confidence: 99%